Rola nieformalnego uczenia się języków obcych w świadomości studentów filologii francuskiej - Grabowska, Monika; Wiater, Aleksander (Neofilolog, 2023)
The aim of this article is to present the results of a survey conducted in the academic year 2021/2022 among students of French Philology Studies at the University of Wroclaw. The subject of interest was the role they attribute to out-of-class language learning (including French) in the process of acquiring communicative competence. The question asked was formulated in such a way as to make students reflect on informal learning situations. Qualitative analysis of the answers indicates a relatively broad spectrum of situations of informal learning, which, due to their complexity, require deeper reflection in order to increase the awareness of not only the effects, but also of the process of lifelong learning and the breadth of learning itself. We postulate that language classes in a formal context have as one of their main purposes the stimulation of such reflection and should invite students to undertake various informal learning activities. This in turn increase the effectiveness of formal teaching/learning, and encourages further reflection on the overall foreign language learning process.